Pathways into childbearing delay of men and women in Australia - Lazzari, Ester (My University, 2022)
Childbearing delay is a pervasive feature of Australian society, but little research has been conducted to examine how socio-economic factors are linked to childbearing timing among Australian men and women. This paper addresses this by analysing the timing of first childbirth for a large sample of Australian residents (N = 4,444). The findings indicate that childbearing delay is socially patterned and that life course experiences shape the risk of delaying childbearing across genders. Having a tertiary qualification delays the transition to parenthood, especially for women. An uninterrupted career prolongs time to parenthood for women but accelerates it for men. Low occupational prestige, being married and having been in only one co-residential union are associated with earlier parenthood for both men and women. For each increase in education level, not being married is associated with increasing levels of childlessness. Clear-cut gender differences are found in the relationship between childlessness and childbearing delay.
Longitudinal and Life Course Studies
Keywords: Families and relationships